2022
DOI: 10.1111/pde.15148
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a lay community health worker (promotoras de salud) program to improve adherence to emollients in Spanish‐speaking Latin American pediatric patients in the United States with atopic dermatitis: A randomized, controlled, evaluator‐blinded study

Abstract: Background: Latin American patients in the United States experience significant health disparities. Community health workers (promotoras de salud) reduce disparities by providing culturally appropriate education. While educational interventions have been studied in atopic dermatitis (AD), a chronic dermatologic condition affecting children, none have evaluated the use of promotoras in Spanish-speaking pediatric patients in the United States. Objective: To create and evaluate a promotora-led education program f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…During MyAlliance development, our community organization partners specifically identified staff training in ADRD as a priority. Numerous studies have demonstrated the efficacy of CHW programs for health education 46,47 . Therefore, we asked partner organizations to help define a curriculum called “Assess.…”
Section: Resultsmentioning
confidence: 99%
“…During MyAlliance development, our community organization partners specifically identified staff training in ADRD as a priority. Numerous studies have demonstrated the efficacy of CHW programs for health education 46,47 . Therefore, we asked partner organizations to help define a curriculum called “Assess.…”
Section: Resultsmentioning
confidence: 99%
“…13,15 For instance, the Medication Event Monitoring Systems (MEMS; Aardex) contains microprocessors that record the date and time when medication bottles are opened. 23 GlowCap and AdhereTech devices are two examples of more recent electronic pill bottle technologies that have the capacity to wirelessly send patient medication adherence data, offering options to analyze and monitor patient medication adherence in real time. 24 However, these proxies for adherence can lead to inaccurate estimates.…”
Section: Measuring Adherencementioning
confidence: 99%
“…54,55 Several studies have been done to assess the association between educational programmes and workshops on patient self-expertise and adherence (Table 2). These interventions, which consistently improved patients' knowledge, 17,23,54,55,64 had mixed results on adherence changes. For example, one study using informational videos and leaflets targeting common misconceptions of topical corticosteroids (TCS) did not increase TCS adherence.…”
Section: Education and Effective Communicationmentioning
confidence: 99%
See 2 more Smart Citations